The Determination of State Budget Governance of Indonesian Public Higher Education Institutions Post COVID-19 Pandemic - Muhammad Alfarizi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
The communication and information openness era, which has become increasingly massive after the COVID-19 Pandemic, has encouraged open relations between the community and state universities in education programs, especially budget management. This study aims to analyze the determination of state university budget management in terms of budget realization, the role of technology, and public information disclosure. This study raises the dimensions of the variable position of technology, perceptions of budget realization, public information disclosure, principles of general financial management, transparency, and accountability concerning managing state finances in universities. Convenience sampling became the technique chosen for sampling and was further analyzed with the SEM-PLS procedure through the SmartPLS application with 237 respondents. This study found the effect of budget realization and public information disclosure in fulfilling the principles of positive public financial management. However, this study does not support the role of technology in supporting the principles of public financial management. This study also notes the positive influence of public financial management principles on state universities' transparency and accountability. This study highlights the maximum future strengthening of higher education budget management with the organizational commitment of higher education institutions under the strict supervision of the government and the community indirectly. Technology does not support it, but it impacts the public in tracing information on Higher Education budget management according to the mandate of various parties, including the Indonesian Supreme Audit Institution.